SEASONAL HABITAT USE AND HOME RANGES OF RIO GRANDE TURKEYS IN OREGON - Thomas W. Keegan; John A. Crawford (Wildlife Society Bulletin)
Abstract: We investigated seasonal habitat use and home ranges of 76 females in a recently established Rio Grande turkey (Meleagris gallopavo intermedia) population in southwestern Oregon from February 1989 through June 1991 to provide information for wildlife and land management activities. Females used all available cover types, but meadows, mixed hardwood–conifer woodlands, and mixed hardwood–conifer savannas were used more often than expected (P ≤ 0.05) during summer (33% of Apr–Sep observations) and winter (56% of Oct–Mar observations). Brushfield, dense sapling–pole mixed conifer, and mature mixed conifer cover types were used less than expected. Annual 95% minimum convex polygon home ranges ranged from 2,784 ha (6,877 ac) for adult females to 5,302 ha (12,429 ac) for yearlings. Females with unsuccessful nests (no eggs hatched) and yearling females moved farther to nest in successive years than did females with successful nests and adult females (P ≤ 0.03). Land managers should consider land management impacts on turkeys at an appropriate scale (>14,000 ha [35,000 ac]) and maintain mixed hardwood–conifer cover types, particularly Oregon white oak (Quercus garryana) woodland and savanna complexes, to benefit wild turkeys in the Pacific Northwest.